The Efficacy of Long Lasting Insecticidal Nets (LLINs) and Insecticide Treated Nets against Anopheles Mosquitoes - Thandar, Aye Mya; Win, Phyo Wai; Htwe, Soe Soe; Mya, Maung Maung (Journal of Diseases, 2019)
Field bio-efficacy of 0, 5, 10, 15 and 20 times washed PermaNet 2.0, Icon LLIN, Deltamethrin and Icon treated cotton and Nylon nets (ITN) against wild caught Anopheles mosquitoes were tested with WHO cone test Kit method in Myaebinthar village Myothit Township, Magwe Region. Mosquitoes were exposed in cones for 5min and 15min fixed exposure period under room temperature in raining and cold season. Knockdown effect was measured after 60 min of exposure. In raining and cold season, a total of 221 and 196 mosquitoes, consist of 8 and 6 species of Anopheles adults were collected. Maximum number of An. culicifacies was caught followed by An vagus in cattle bate k net, human bait and lowest was collected in morning resting collection. In both season maximum number of main vector An. minimus was caught on human and cattle bait collection between 21:00 and 24:00hours. The bio efficacy of 0 and 5 washed all PermaNet 2.0, Icon and deltamethrin LLINs and ITNs found 100% knockdown ability with all caught mosquitoes. An.minimus and An.culicifacies found to be 80-100% knockdown effect against 10washes with PermaNet 2.0 and Icon LLINs in both season. Knockdown efficacy was significantly declined between 5 and 20washes,100-60% knockdown on LLINs and 90-20% for Deltamethrin and Icon treated nets in both season. PermaNet 2.0, Icon LLINs were found higher wash resistance ability till 15 washes than deltamethrin and Icon treated cotton net but nylon net was found lowest wash resistance needs repeated treatment.